2019
DOI: 10.1002/apj.2365
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on the influence of nozzle–organization–mode of split burner on flow field distribution and combustion characteristics of a 300‐MWe subcritical down‐fired boiler

Abstract: Numerical simulations are carried out to investigate the influence of burner nozzle–organization–mode (N–O–M) on flow field distribution and combustion characteristics of a 300‐MWe subcritical down‐fired boiler. Three typical N–O–Ms respectively designed with Mitsui Babcock Energy Limited (MBEL), fuel‐lean coal/air flow down‐setting (FD), and multi‐injection multistaging combustion (MIMSC) technology are studied, plus industrial‐size measurements on the original MBEL boiler. Vertical velocity attenuation index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The inlet and outlet conditions were set as speed inlet, and the outlet condition was set as pressure outlet. The above models and methodologies are conventional and have wide applicability in modeling coal combustion 8,23,24,28–31 . Consequently, the information about the related calculation equations is not provided here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inlet and outlet conditions were set as speed inlet, and the outlet condition was set as pressure outlet. The above models and methodologies are conventional and have wide applicability in modeling coal combustion 8,23,24,28–31 . Consequently, the information about the related calculation equations is not provided here.…”
Section: Methodsmentioning
confidence: 99%
“…The above models and methodologies are conventional and have wide applicability in modeling coal combustion. 8,23,24,[28][29][30][31] Consequently, the information about the related calculation equations is not provided here. The W-shaped flame furnace owns a symmetrical structure along the centerline in the furnace width direction, where each group of burners presents the relatively independent combustion conditions.…”
Section: Air-regulating Solutions Ofa Ratio Setups and Simulation Met...mentioning
confidence: 99%
“…Subsequently, an improved version of the MIMSCT (i.e., performing a further burner nozzle layout optimization to fit for different down-fired furnace types) was popularized in several furnaces. [15][16][17] Ma et al 18 proposed a low-NO x art for a 600-MW e directflow-burner furnace via rearranging burners and introducing OFA to deepen air staging, finally gaining NO x levels of about 800 mg/m 3 (6% O 2 ) while worsening burnout a little. Chen et al 19 achieved a similar low-NO x accomplishment in a 600-MW e swirl-flow-burner furnace by altering the burner arrangement and using a separated OFA form.…”
Section: Introductionmentioning
confidence: 99%
“…For a multiple‐injection multiple‐staging combustion technology (MIMSCT) focused on high NO x generation plus asymmetric combustion, 14 its first industrial‐size trial in a 600‐MW e boiler achieved a moderate low‐NO x performance, that is, NO x production at 867 mg/m 3 (6% O 2 ) plus carbon content in fly ash at 5.4%. Subsequently, an improved version of the MIMSCT (i.e., performing a further burner nozzle layout optimization to fit for different down‐fired furnace types) was popularized in several furnaces 15–17 . Ma et al 18 proposed a low‐NO x art for a 600‐MW e direct‐flow‐burner furnace via rearranging burners and introducing OFA to deepen air staging, finally gaining NO x levels of about 800 mg/m 3 (6% O 2 ) while worsening burnout a little.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rich reserves of low‐volatile coals and a large proportion of these coals in total coal consumption for thermal power generation, W‐shaped flame furnaces have popularized well in China since the first import from Britain in the late 1980s 3 . However, actual operations have shown that there exist universal problems of late coal ignition, unstable combustion, asymmetric combustion, high burnout loss (carbon content in fly ash above 8%), severe slagging, and high NO x emissions (conventionally higher than 1,100 mg/m 3 at 6% O 2 ) 4–6 . Accordingly, various investigations or solutions have been reported via the methods referred to real‐furnace measurements, lab‐scale cold‐modeling experiments, and numerical simulations 7 …”
Section: Introductionmentioning
confidence: 99%